A Review on Indian Economic Growth and Liberalization (International Journal of Innovative Research in Engineering & Management, 2021)
As seen in the preceding portions, India's rise during the  1980s does not give an example of Asian state-led growth.  Instead, they must be used by the quick availability of new  technologies and the qualified personnel. The utilization of  these new technologies the technology transfer was largely  achieved through improved and cheaper access to imported  machines via trade liberalization in the 1980s and early 1990s.  Additional technologies that have been key drivers of  development since the mid-1990s have improved cellular  connection and Internet distribution. In India, a revolution in  communication technology cannot have been achieved  without the breakdown of state monopolies and the  development of competition in the communication business.  India would not have taken the fastest-growing industries out  of this transition. Obviously, the ongoing progress that we  have witnessed since the mid-1990 without the 1991  liberalization measures was not possible. We can recognize  that liberalization policies are significant if one thinks that  India is still subject to restrictions on enterprise free  investment and imports, which were pre-reformed.
Keywords: Economic; Growth; Industries; Liberalization; Technology